Strategies of Grouping Cooperative Learning in High School Mathematics under the New Curriculum Reform - Guo, Yunxing (Journal of Education and Educational Technologies, 2023)
The teaching of mathematical modeling belongs to systematic engineering and requires coordination among various departments in universities. For example, a local university has established a mathematics modeling teaching and competition committee, which is mainly responsible for coordinating and managing the content of mathematics modeling teaching or learning in the school. Responsible for training and participating in annual mathematical modeling competitions, as well as promoting the teaching and learning of mathematical modeling throughout the school. At the same time, he is also responsible for managing the mathematical modeling laboratory and establishing a special fund for mathematical modeling. The university conducted training on modeling competitions from October last year to June this year, and also guided students to learn mathematical modeling courses through the establishment of public elective courses. For example, setting up subjects such as "Mathematical Modeling" and "Mathematical Modeling". During the holiday enhancement phase, the school strengthened the students' ability to understand and apply mathematical modeling knowledge by expanding mathematical modeling research methods, such as graph theory, Operations research, hierarchical analysis, fuzzy mathematics and other subjects, and by explaining computer programming, national contest analysis, paper writing, Matlab and other mathematical software use, so as to prepare for the subsequent mathematical modeling contest.